Relentless : Brick Kavanagh Mystery #1 - Wilson, Shawn (Novelist) (Sarasota, Florida : Oceanview Publishing, 2019)
"Cherry blossom season is Washington, D.C.'s most beautiful time of the year. But as tourists flock to the city, this year's festivities are marred by the discovery of the naked body of a young woman floating in the Tidal Basin. Veteran homicide detective Brian (Brick) Kavanagh is assigned to the case. He's shocked when he learns the victim is connected to another homicide which makes the investigation very personal for him. Brick's efforts to solve the case are thwarted by departmental politics and a rush to judgment. Convinced that justice has not been served and the wrong person is in jail, Kavanagh risks all to relentlessly pursue the truth. Overlooked evidence ultimately leads to a devastating conclusion in a heartbreaking case."--Publisher description.
Keywords: Police -- Washington (D C ) -- Fiction; Murder -- Fiction; Homicide investigation -- Fiction; Homicide investigation; Murder; Police; Washington (D.C.) -- Fiction; Washington (D.C.) -- Fiction; Washington (D.C.); Detective and mystery fiction; Fiction; Thriller fiction; Detective fiction; Mystery fiction